A stable super-amphiphilic surface created from superhydrophobic silica/epoxy coating by low-temperature plasma-treatment. (3rd October 2021) - Li, Xia; Yang, Jingxia; Wang, Jinjie; Chang, Xijiang; Xu, Jingli; Wu, Zhonghang
ABSTRACT: A silica/epoxy hydrophobic coating (water contact angel (WCA) = 130°) was prepared on a glass substrate and further treated in a low-temperature plasma (PL) condition, which surprisingly resulted in an amphiphilic surface (best WCA = 3.5°, best oil CA = 5°) with excellent surface stability and without decay along with the time. We systematically studied the influences of two working gases (O2, Ar) and the working time of PL-treatment on the wetting behaviour (for both water and oil) and the aging effects of the PL-treated silica/epoxy coating, using SEM, FTIR-ATR, XPS and metallographic microscope. The results suggested that the stable super-amphiphilic change, causing by O2 or Ar low-temperature PL-treatment, can be attributed to a physical smoother surface (bombed by PL-treatment) and the surface chemical state change (more polar groups, OH/NH2 ).